When to initiate integrative neuromuscular training to reduce sports-related injuries in youth? - Myer, Gregory D. (2011)
Regular participation in organized youth sports does not ensure adequate exposure to skill- and health-related fitness activities; and sport training without preparatory conditioning does not appear to reduce risk of injury in young athletes. Recent trends indicate that widespread participation in organized youth sports is occurring at a younger age, especially in girls. Current public health recommendations developed to promote muscle strengthening and bone building activities for youth aged 6 and older, along with increased involvement in competitive sport activities at younger ages, has increased interest and concern from parents, clinicians, coaches and teachers regarding the optimal age to encourage and integrate more specialized physical training into youth development programs. This review synthesizes the latest literature and expert opinion regarding when to initiate neuromuscular conditioning in youth and presents a how to integrative training conceptual model that could maximize the potential health-related benefits for children by reducing sports-related injury risk and encouraging lifelong regular physical activity.